Implementasi SAK EMKM Terhadap UMKM di Kota Pontianak (Studi Kasus Pada FT Laundry) - Namira, Aulia; Azmi, Ika Nur; Indah, Djunita Permata (Universitas Teuku Umar, 2024)
The majority of businesses in Indonesia are micro, small and medium enterprises (MSMEs). Due to their presence in various sectors, MSMEs play an important role in driving the country's economy. Nonetheless, MSMEs face obstacles and lack of understanding in following the Financial Accounting Standard for Micro, Small, and Medium Entities (SAK EMKM) which highlights the importance of preparing financial statements. This study aims to investigate how FT Laundry MSMEs prepare their financial statements whether they are in accordance with SAK EMKM standards through a qualitative research approach involving document analysis, interviews, and observations. Data was analyzed using the methods of information collection, data reduction, data presentation, and conclusion drawing. Based on the research findings, it appears that owners of laundry businesses still rely on traditional accounting methods for their financial records and do not adopt the SAK EMKM financial reporting system. The main reasons why these businesses do not adopt SAK EMKM include a lack of understanding of the system, a lack of manpower who can prepare reports in accordance with SAK EMKM guidelines, and a lack of awareness of the importance of preparing reports in accordance with the standard.